DETEKSI EFEK GEMPABUMI PADA IONOSFER MENGGUNAKAN DATA GNSS - Anwar Santoso; Buldan Muslim; Siti Inayah Fitriyani (Komunikasi Fisika Indonesia, 2020)
Seismic activities such as earthquakes can cause atmospheric and infrared gravitational waves. If the earthquake happens to be strong enough (M> 6 SR), these waves can spread to the ionosphere altitude in the form of atmospheric and infrasonic gravitational waves. The monitoring system of ionospheric wave that associated with earthquakes from network of GNSS data has been much developed in Indonesia by using the sliding Fast Fourier Transform (SFFT) programfor disturbed ionospheric TEC positions. The results of previous studies, differential TEC showed irregular fluctuations in the order of several tens of seconds until to several tens of minutes with average amplitude less than 0.01 TECU. At times the ionospheric is not disturbed (regular), the amplitude can reaching greater than 0.01 TECU. As a case study, in this paper a methodological examination will be conducted on the events of Aceh earthquake on December 26, 2004 (M = 9.2 SR), Tohoku March 11, 2011 (M = 9 SR) and Yogyakarta May 27, 2006 (M = 6.2 SR).